Emerging Legal Frontiers in Insurance Digital Transformation, Cross-Border Challenges, and Market Innovation - Marano, Pierpaolo; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book offers a forward-looking analysis of how digital disruption and cross-border dynamics are reshaping insurance law. Further, it shares legal and regulatory insights into the challenges posed by new technologies and evolving market structures. The first section explores digital realities$1 (Bfrom insurance in the metaverse and robo-advisers to blockchain-based duties and the role of copyright law in digital distribution. In turn, the second section discusses jurisdictional and cross-border issues, including barriers to life insurance passporting, fairness in group insurance, brokers co-opetition, and the influence of EU soft law on national markets. These topics are highly relevant, as they reflect the real-world pressures on legal systems to adapt to innovation while maintaining fairness, accountability, and coherence. The book addresses the regulatory and legal gaps emerging from this transformation, helping readers navigate the resulting complexities and uncertainties. Given its scope, it will be of interest to legal scholars, regulators, practitioners, and advanced students in the fields of insurance law, financial regulation, and digital governance.s
Part I $1 (BDigital Realities and Technological Disruptions in Insurance Law -- 1. The Legal Challenges Surrounding Transactions in the Metaverse: The Case of Insurance -- 2. Bringing Trustworthy Robo-Advisers into the Insurance Distribution Process: An Accountability Perspective -- 3. Chinese Perspective on Representation Duty in Blockchain-Based Insurance -- 4.The Impact of Copyright Law on Insurance Distribution: The Development of the Insurance Market within Economic Efficiency/Inefficiency of Copyright Monopolies -- Part II $1 (BJurisdictional Perspectives and Cross-Border Insurance Market Dynamics -- 5. Cross-Border (Life) Insurance Business: A Constant Goal with (Almost) Impossible Legal Obstacles -- 6. Group Insurance in Comparative Perspective: Ensuring Fairness, Efficiency, and Beyond -- 7. Legal and Economic Aspects of Co-operation of Insurance Brokers: The Polish Case -- 8. The Importance of EU Soft Law in Insurance Distribution: The Case of Poland.s
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Information technology -- Law and legislation; Mass media -- Law and legislation; Private international law; Conflict of laws; International law; Comparative law; Commercial law; European Economic Community; Finance -- Law and legislation; IT Law, Media Law, Intellectual Property; Private International Law, International and Foreign Law, Comparative Law; European Economic Law; Financial Law